2019
DOI: 10.5014/ajot.2019.73s1-po2029
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Financial Literacy for Homeless Teens Through a Leisure-Based OT Program

Abstract: Date Presented 04/04/19 This pretest-posttest quasi-experimental pilot investigation used a client-centered outcomes measure, Goal Attainment Scaling (GAS), to identify gains achieved following attendance to OT sessions focused on financial literacy for teens living in a homeless shelter. The teens collaborated with graduate OT students to develop goals and then identified the self-perceived gains following participation in the group sessions. Primary Author and Speaker: Anna Shav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…It is suggested that OTs use a validated measure such as the Financial Knowledge Scale (Bajaj & Kaur, 2021) to determine the participants’ financial knowledge. The Goal Attainment Scale can also be used to measure individual gains in financial literacy (Shaver et al, 2019). The financial literacy program can be provided in weekly sessions focusing on instruction in specific financial literacy skills and then applying those skills in a client-centered life skills activity like cooking, banking, or leisure pursuit.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is suggested that OTs use a validated measure such as the Financial Knowledge Scale (Bajaj & Kaur, 2021) to determine the participants’ financial knowledge. The Goal Attainment Scale can also be used to measure individual gains in financial literacy (Shaver et al, 2019). The financial literacy program can be provided in weekly sessions focusing on instruction in specific financial literacy skills and then applying those skills in a client-centered life skills activity like cooking, banking, or leisure pursuit.…”
Section: Discussionmentioning
confidence: 99%
“…The study had a limited sample size, but the participants reported that the two skills they gained included creating a monthly budget and prioritizing necessary versus optional spending (Gardner et al, 2019). Leisure-based activities were used by occupational therapists in two quasi-experimental studies to help 12- to 17-year-old homeless adolescents acquire financial literacy skills, four in one study, and five in another (Schultz-Krohn et al, 2018; Shaver et al, 2019). Participants in these low-powered studies demonstrated improvement in financial acumen following participation in an OT group as measured using the Goal Attainment Scale (Schultz-Krohn et al, 2018; Shaver et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations